Indonesian Foreign Policy In Maintaining Multilateral Relations of APEC Members - Abdurofiq, Atep; Putra, Gilang Rizki Aji; Yunus, Nur Rohim (BULETIN ADALAH, 2024)
Indonesia's proactive foreign policy has dramatically impacted the Asia-Pacific Economic Cooperation (APEC) group's (APEC) worldwide relationship. Due to its active foreign policy, Indonesia can make judgments and formulate plans that are in line with its national interests, free from the influence of political blocs that are driven by dominance. Indonesia's aggressive foreign policy has contributed to the country's growing importance outside of APEC. With 21 member nations cooperating to support steady economic growth in Asia-Pacific, APEC has become a prominent participant in the world economy. In addition to its active participation in international financial institutions like the World Bank and Asian Development Bank, Indonesia's active foreign policy has contributed to its status as a significant participant in global monetary and fiscal affairs.